Relationship Between Cerebral Hemodynamics, Tissue Oxygen Saturation, and Delirium in Patients With Septic Shock: A Pilot Observational Cohort Study - Feng, Qing; Ai, Meilin; Huang, Li; Peng, Qianyi; Ai, Yuhang; Zhang, Lina (Frontiers in Medicine, 2021)
Background Septic shock patients have tendencies towards impairment in cerebral autoregulation and imbalanced cerebral oxygen metabolism. Tissue oxygen saturation and Transcranial Doppler (TCD) monitoring were undertaken for observation of the variations of middle cerebral artery cerebral hemodynamic indices and also of cerebral/peripheral tissue oxygen saturation (StO2) in order to discover factors that increase the probability of sepsis-associated delirium (SAD). Materials and Methods The research cohort was chosen from septic shock patients received in the Department of Critical Care Medicine of Xiangya Hospital, Central South University, between May 2018 and March 2019. These patients were separated into two groups, SAD and non-SAD as assessed using the Confusion Assessment Method for the Intensive Care Unit (CAM-ICU). Comparisons were made between the two groups in terms of peripheral tissue oxygen saturation, fluctuations in regional cerebral oxygen saturation, cerebral vascular automatic regulation function (transient hyperemia response rate, THRR index), cerebral hemodynamic index, organ function indicators, blood gas analysis indices, and patient characteristics. Results 39% of the patients (20/51) suffered SAD. 43% of the patients died within 28 days of admission (22/51). Individuals in the SAD cohort needed a longer period of mechanical ventilation (5 days [95% CI 2, 6] against 1 day [95% CI 1, 4], p= 0.015), more time in ICU (9 days [95% CI 5, 20] against 5 those [95% CI 3, 9], p= 0.042); they also experienced more deaths over the 28-day period (65% against 29%, p= 0.011). Multivariate regression analysis indicated that independent variables associated with SAD were THRR index (OR = 5.770, 95% CI: 1.222-27.255; p= 0.027) and the mean value for regional cerebral oxygen saturation (rSO2) <55% (OR = 3.864, 95% CI: 1.026-14.550; p = 0.046). Conclusions Independent risk factors for SAD were mean cerebral oxygen saturation below 55% and cerebrovascular dysregulation (THRR<1.09).